2009
DOI: 10.1088/0022-3727/42/18/185410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron doping on electrical, electronic and magnetic properties of La0.7Sr0.3MnO3

Abstract: The effect of 5% Fe doping at Mn site, on the valence band structure of La0.7Sr0.3MnO3 has been investigated. Polycrystalline samples of La0.7Sr0.3MnO3 and La0.7Sr0.3Mn0.95Fe0.05O3 have been prepared by the solid-state reaction route. The phase purity of these samples was confirmed using x-ray diffraction. Core-level x-ray photoelectron spectroscopy measurements were performed to study the changes in the chemical composition. The valence band spectroscopy measurements on these samples, using a synchrotron radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…From the figure, it can be seen that there is overlap between e g states (A) and O 2p (C), which demonstrates the hybridization of these orbitals. This result is same as that of La 0.7 Sr 0.3 MnO 3 reported elsewhere [20] . For x=0.19 sample, the area of overlap between e g states (A) and O 2p (C) is a little larger than that of x=0.17 sample, which means a higher degree of hybridization of these orbitals.…”
Section: Contributed Articlesupporting
confidence: 92%
“…From the figure, it can be seen that there is overlap between e g states (A) and O 2p (C), which demonstrates the hybridization of these orbitals. This result is same as that of La 0.7 Sr 0.3 MnO 3 reported elsewhere [20] . For x=0.19 sample, the area of overlap between e g states (A) and O 2p (C) is a little larger than that of x=0.17 sample, which means a higher degree of hybridization of these orbitals.…”
Section: Contributed Articlesupporting
confidence: 92%
“…It is evident from the inset of Fig. 3(a) that there is a deviation from CurieeWeiss behaviour in the paramagnetic (PM) region for the LCMFe 0.05 possibly due to the increase in magnetic moment arising from the nucleation of super paramagnetic clusters in the PM region [44]. Ferromagnetic coupling between adjacent nano crystalline clusters result in observed increase in the average moment of the superparamagnetic particles with decrease in temperature.…”
Section: Superparamagnetic Statementioning
confidence: 90%
“…This is attributed to the antiferromagnetic alignments of spins between Mn and Fe ions [43]. Deshmukh et al [44] have reported such a decrease in Fe substituted La 0.7 Sr 0.3 MnO 3 . The MeH curve of LCMFe 0.05 shows the typical behaviour for superparamagnetic (SPM) particles and can be well fitted with Langevin function (Eq.…”
Section: Superparamagnetic Statementioning
confidence: 93%
“…Further, extensive efforts are underway in different laboratories to enhance the magnitude of magnetoresistance at low fields, particularly in milli and micro Tesla range using techniques such as artificial grain boundaries and tunnel junctions [1,2]. Although a lot of work on Re 0.67 A 0.33 MnO 3 [where Re is La, Nd, Pr, etc., and A is Ca, Sr, Ba, etc.,] manganites has been published [3][4][5], the physical origin behind the conduction mechanism and its correlation with magnetoresistance, especially at low temperatures is still elusive. Therefore, the electrical resistivity studies will be interesting and important.…”
Section: Introductionmentioning
confidence: 99%